MiR-34b-5p Suppresses Melanoma Differentiation-Associated Gene 5 (MDA5) Signaling Pathway to Promote Avian Leukosis Virus Subgroup J (ALV-J)-Infected Cells Proliferaction and ALV-J Replication - Li, Zhenhui; Luo, Qingbin; Xu, Haiping; Zheng, Ming; Abdalla, Bahareldin Ali; Feng, Min; Cai, Bolin; Zhang, Xiaocui; Nie, Qinghua; Zhang, Xiquan (Frontiers in Cellular and Infection Microbiology, 2017)
Avian leukosis virus subgroup J (ALV-J) is an oncogenic retrovirus that has a similar replication cycle to multiple viruses and therefore can be used as a model system for viral entry into host cells. However, there are few reports on the genes or microRNAs (miRNAs) that are responsible for the replication of ALV-J. Our previous miRNA and RNA sequencing data showed that the expression of miR-34b-5p was significantly upregulated in ALV-J-infected chicken spleens compared to non-infected chicken spleens, but melanoma differentiation-associated gene 5 (MDA5) had the opposite expression pattern. In this study, a dual-luciferase reporter assay showed that MDA5 is a direct target of miR-34b-5p. In vitro, overexpression of miR-34b-5p accelerated the proliferation of ALV-J-infected cells by inducing the progression from G2 to S phase and it promoted cell migration. Ectopic expression of MDA5 inhibited ALV-J-infected cell proliferation, the cell cycle and cell migration, and knockdown of MDA5 promoted proliferation, the cell cycle and migration. In addition, during ALV-J infections, MDA5 can detect virus invasion and it triggers the MDA5 signaling pathway. MDA5 overexpression can activate the MDA5 signaling pathway, and thus it can inhibit the mRNA and protein expression of the ALV-J env gene and it can suppress virion secretion. In contrast, in response to the knockdown of MDA5 by small interfering RNA (siRNA) or an miR-34b-5p mimic, genes in the MDA5 signaling pathway were significantly downregulated (P < 0.05), but the mRNA and protein expression of ALV-J env and the sample-to-positive ratio of virion in the supernatants were increased. This indicates that miR-34b-5p is able to trigger the MDA5 signaling pathway and affect ALV-J infections. Together, these results suggest that miR-34b-5p targets MDA5 to accelerate the proliferation and migration of ALV-J-infected cells, and it promotes ALV-J replication, via the MDA5 signaling pathway.